Eine Methode zur Anpassung und Auswertung von MRT- und SPECT-Schnittbildern zum Vergleich von zerebraler Morphologie mit zerebrovaskulärer Regulation - Kaiser, H.-J.; Reiche, W.; Büll, U. (Nuklearmedizin - NuclearMedicine, 1990)
A method is introduced which yields computerized correlations of topographically identical morphological and functional orbito-meatal slices of the brain by employing the specific local resolutions and a simple adaption algorithm. In addition, a ROI-overlay method is described which may be used to evaluate semiquantitatively (interhemispherical ratios or ratios hemisphere/cerebellum) identical planes to assess rCBF, rCBV and regional vascular regulation. It appears to be advantageous that ROIs can be superimposed on MRI images as well as on SPECT images.